Melatonin modulates the gene expression of WEE1 kinase and clock genes: a crosstalk between the molecular clocks of the placenta? - Venegas, Carlos; Jara-Medina, Kevins; Cueto, Nicole; Cabello-Guzmán, Gerardo; Lagunas, Constanza; Lillo, Luis; Valenzuela-Melgarejo, Francisco J. (Frontiers in Endocrinology, 2025)
BackgroundThe circadian system organizes during 24 hours the temporal variations in biological processes such as the cell cycle, metabolism, and hormone production. This occurs by a transcriptional/translational feedback loop of core clock genes, namely, BMAL1, PER1-3, and CRY1-2. The CLOCK–BMAL1 complex regulates clock-controlled genes like WEE1 kinase, a key modulator of mitotic entry and placental cell proliferation.ObjectiveWe aimed to identify temporally regulated gene expression patterns in the human placenta using bioinformatics analysis of available microarrays in Gene Expression Omnibus (GEO) datasets and to validate selected findings in cultured placental explants.MethodsTemporal microarray data from the GEO were analyzed to identify circadian and cell cycle-related genes. Selected targets were validated in vitro using explant cultures of human placenta sampled every 4 hours for 36 hours, with or without 10 nM melatonin.ResultsWe observed rhythmic expression of BMAL1, PER1, PER2, and WEE1 in human placental explants, consistent with the temporal patterns detected in silico. Melatonin treatment suppressed the circadian oscillation of BMAL1, PER2, and WEE1. Interestingly, the placenta produced melatonin steadily over 36 hours, and exogenous melatonin did not alter this production.